(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
My aim is to extend the notion of gray zone, presented by Claire Bishop in her 2018 essay, Black Box, White Cube, Gray Zone, through that of skilled intentionality, proposed by Erik Rietveld and colleagues (Rietveld, Denys, Van Westen, 2018) in the field of embodied cognitive science. Starting, thus, from an ecological-enactive approach to cognition, I will present the notion of skilled co-presence through which I try to shed light on how we are able to extend our abilities by hybridizing with others, materials, and technologies. To do this I will rest my reflection on the notion of autopoietic feedback loop presented by Erika Fisher-Lichte (Fisher-Lichte, 2008). Rietveld and colleagues’ proposal revolves around the enrichment of the notion of affordance (Gibson 1979, Rietveld,Kiverstein 2014), understood as the relationship between an aspect of the sociomaterial environment and the abilities available in a life form. New affordances emerge when aspects of the material environment are captured by skills usually used in other practices. I believe that at the emergence of a gray zone, it is possible to observe, in a paradigmatic way, how new skills can arise through pooling and cross-fertilization.